1995
DOI: 10.1021/bi00010a016
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function in rhodopsin. Separation and characterization of the correctly folded and misfolded opsins produced on expression of an opsin mutant gene containing only the native intradiscal cysteine codons

Abstract: Previous mutagenesis studies have indicated the requirement of a tertiary structure in the intradiscal region with a disulfide bond between Cys-110 and Cys-187 for the correct assembly and/or function of rhodopsin. We have now studied a rhodopsin mutant in which only the natural intradiscal cysteines at positions 110, 185, and 187 are present while all the remaining seven cysteines in the wild-type bovine rhodopsin have been replaced by serines. The proteins formed on expression of this mutant in COS-1 cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 34 publications
3
78
0
Order By: Relevance
“…We note that although the Arg-177 and Asp-190 residues point away from the helical bundle, it is also possible that mutations to this ion pair may affect the positioning or orientation of helices 5 and 6. However, there is some precedence for conformational changes in loop E-2, as Ridge et al (77) initially interpreted our results to mean that disrupting the Arg-177/Asp-190 ion pair causes a loosening of the loop E-2 structure, and thus we hypothesized the increased rate of Schiff base hydrolysis was due its increased exposure to external solvent. However, to our surprise, we found that the presence of 50 mM hydroxylamine had no effect on any of the mutants tested, even when tested at three different temperatures (Fig.…”
Section: Arrhenius Analysis Indicates the Thermal Decay In Rhodopsin mentioning
confidence: 82%
“…We note that although the Arg-177 and Asp-190 residues point away from the helical bundle, it is also possible that mutations to this ion pair may affect the positioning or orientation of helices 5 and 6. However, there is some precedence for conformational changes in loop E-2, as Ridge et al (77) initially interpreted our results to mean that disrupting the Arg-177/Asp-190 ion pair causes a loosening of the loop E-2 structure, and thus we hypothesized the increased rate of Schiff base hydrolysis was due its increased exposure to external solvent. However, to our surprise, we found that the presence of 50 mM hydroxylamine had no effect on any of the mutants tested, even when tested at three different temperatures (Fig.…”
Section: Arrhenius Analysis Indicates the Thermal Decay In Rhodopsin mentioning
confidence: 82%
“…Forty-eight hours after tetracycline induction, HEK-293 cells expressing WT opsin were harvested and incubated with both 9-and 11-cis-retinals. The rhodopsin formed was purified by immunoaffinity chromatography under conditions that selectively release folded opsin (19), and the first eluted fraction was examined by UV-visible spectroscopy and HPLC. The pigment obtained in post-harvest regeneration of WT opsin with 9-cis-retinal has a shifted absorption spectrum with max Ï­ 487 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For convenience, the numbering of the mutants has been changed from that in the original paper (8) as in Table 1. All the mutant genes were expressed in COS-1 cells and purified by absorption on antirhodopsin 1D4-Sepharose as described (11,13). In addition, the deletion and sequence replacement mutants in Table 1 were prepared by expression in stable mammalian cell lines (14).…”
Section: Methodsmentioning
confidence: 99%